A Volume-Surface Integral Equation Solver for Radiation from Microstrip Antenna on Anisotropic Substrate - Yuhuang Ye; Jiade Yuan; Kaixiong Su (International Journal of Antennas and Propagation)
A volume-surface integral equation (VSIE) solver is presented for the calculation of electromagnetic radiation from arbitrary shaped microstrip antenna on anisotropic substrate. The method of moments (MoM) is used to convert the integral equation into a matrix equation, where the equivalent volume current and surface current are expanded into a finite series of SWG and RWG basis function, respectively. A simple strip model is incorporated in the VSIE to simplify the analysis of the probe-fed microstrip antenna. The present approach is sufficiently versatile in handling microstrip antenna with arbitrary shaped anisotropic dielectric substrate. Numerical results indicate the reliability and accuracy of the proposed method.